Structure of block copolymer grafted silica nanoparticles. (20th December 2018) - Goel, Vivek; Pietrasik, Joanna; Poling-Skutvik, Ryan; Jackson, Andrew; Matyjaszewski, Krzysztof; Krishnamoorti, Ramanan
Abstract: The morphology of a block copolymer of a near symmetric strongly-segregating poly( n -butyl acrylate) and poly(methyl methacrylate) tethered to a ∼15 nm silica nanoparticles is examined using a combination of microscopy techniques and small angle x-ray and neutron scattering. The copolymer components are strongly segregated and form a disordered structure that is possibly a combination of coexisting individual randomly placed core-shell structures and worm-like cylinders with 3–5 silica nanoparticles forming the core. With increasing temperature, the cylinders become shorter because of the improved thermodynamic compatibility between the two copolymer segments. Graphical abstract: Highlights: The morphology of a block copolymer of a near symmetric strongly-segregating poly( n -butyl acrylate) and poly(methyl methacrylate) tethered to a ∼15 nm silica nanoparticles is examined. The copolymer components are strongly segregated and the nanoparticle hybrid forms a disordered structure that is a combination of coexisting individual randomly placed core-shell structures and worm-like cylinders with 3–5 silica nanoparticles forming the core of the cylinder. With increasing temperature, the cylinders become shorter.